Measurement‐based range evaluation for quality assurance of CBCT‐based dose calculations in adaptive proton therapy. Issue 8 (29th June 2021) - Neppl, Sebastian; Kurz, Christopher; Köpl, Daniel; Yohannes, Indra; Schneider, Moritz; Bondesson, David; Rabe, Moritz; Belka, Claus; Dietrich, Olaf; Landry, Guillaume; Parodi, Katia; Kamp, Florian
Abstract : Purpose: The implementation of volumetric in‐room imaging for online adaptive radiotherapy makes extensive testing of this image data for treatment planning necessary. Especially for proton beams the higher sensitivity to stopping power properties of the tissue results in more stringent requirements. Current approaches mainly focus on recalculation of the plans on the new image data, lacking experimental verification, and ignoring the impact on the plan re‐optimization process. The aim of this study was to use gel and film dosimetry coupled with a three‐dimensional (3D) printed head phantom (based on the planning CT of the patient) for 3D range verification of intensity‐corrected cone beam computed tomography (CBCT) image data for adaptive proton therapy. Methods: Single field uniform dose pencil beam scanning proton plans were optimized for three different patients on the patients' planning CT (planCT) and the patients' intensity‐corrected CBCT (scCBCT) for the same target volume using the same optimization constraints. The CBCTs were corrected on projection level using the planCT as a prior. The dose optimized on planCT and recalculated on scCBCT was compared in terms of proton range differences (80% distal fall‐off, recalculation). Moreover, the dose distribution resulting from recalculation of the scCBCT‐optimized plan on the planCT and the original planCT dose distribution were compared (simulation). Finally, the two plans of each patient were irradiated on the corresponding patient‐specific 3D printed head phantom using gel dosimetry inserts for one patient and film dosimetry for all three patients. Range differences were extracted from the measured dose distributions. The measured and the simulated range differences were corrected for range differences originating from the initial plans and evaluated. Results: The simulation approach showed high agreement with the standard recalculation approach. The median values of the range differences of these two methods agreed within 0.1 mm and the interquartile ranges (IQRs) within 0.3 mm for all three patients. The range differences of the film measurement were accurately matching with the simulation approach in the film plane. The median values of these range differences deviated less than 0.1 mm and the IQRs less than 0.4 mm. For the full 3D evaluation of the gel range differences, the median value and IQR matched those of the simulation approach within 0.7 and 0.5 mm, respectively. scCBCT‐ and planCT‐based dose distributions were found to have a range agreement better than 3 mm (median and IQR) for all considered scenarios (recalculation, simulation, and measurement). Conclusions: The results of this initial study indicate that an online adaptive proton workflow based on scatter‐corrected CBCT image data for head irradiations is feasible. The novel presented measurement‐ and simulation‐based method was shown to be equivalent to the standard literature recalculation approach. Additionally, it has the capability to catch effects of image differences on the treatment plan optimization. This makes the measurement‐based approach particularly interesting for quality assurance of CBCT‐based online adaptive proton therapy. The observed uncertainties could be kept within those of the registration and positioning. The proposed validation could also be applied for other alternative in‐room images, e.g. for MR‐based pseudoCTs.